Prioritizing occupants understanding level on residential building energy consumption - Suleiman, Jibrin Hassan (Penerbit UTM Press, 2015)
The building sector is widely known for its greenhouse gas and carbon emission which is very significant to the global warming as observed in recent years. Many research works highlighted that buildings has a negative impact on the society as it consumes up to 80% of the total energy used during operation stage. In Malaysia, electricity energy consumption in buildings is 63,354GWh out of the total 116,353GWh of total energy consumed in the country in the year 2012. This paper consider the understanding level of the residential owners in their building energy usage at their various residential buildings. Energy use by household varies widely, this is due to the living standard of a country, type of buildings and climate condition of the region. The study is based on the tips and guides to energy efficiency at home of the Sustainable Energy Development Authority (SEDA) Malaysia. Data was collected through a questionnaire survey form and was analyzed using regression analysis, the results indicates that the occupants have little or no proper understanding of Air-condition, Home appliance and Lighting appliances.